90.6k views
1 vote
2 7 5
- -4x+ - = -9x+ -
3 2 6

2 7 5 - -4x+ - = -9x+ - 3 2 6-example-1
User Icehawk
by
5.9k points

2 Answers

5 votes

Answer:

x= -2/3

alternate form

×= -0.6

User Dustin Brownell
by
7.3k points
3 votes

Answer:


x = (2)/(3)

Explanation:

Let's solve your equation step-by-step.

2

3

−4x+

7

2

=−9x+

5

6

Step 1: Simplify both sides of the equation.

2

3

−4x+

7

2

=−9x+

5

6

2

3

+−4x+

7

2

=−9x+

5

6

(−4x)+(

2

3

+

7

2

)=−9x+

5

6

(Combine Like Terms)

−4x+

25

6

=−9x+

5

6

−4x+

25

6

=−9x+

5

6

Step 2: Add 9x to both sides.

−4x+

25

6

+9x=−9x+

5

6

+9x

5x+

25

6

=

5

6

Step 3: Subtract 25/6 from both sides.

5x+

25

6

25

6

=

5

6

25

6

5x=

−10

3

Step 4: Divide both sides by 5.

5x

5

=

−10

3

5

x=

−2

3

User Abaghel
by
6.0k points